PENINGKATAN KANDUNGAN NUTRIENT RUMPUT KUME (SORGHUM PLUMOSUM VAR. TIMORENSE) KERING YANG DIFERMENTASI DENGAN PROBIOTIK STARBIO - W. M.S.M. Emma; A. Paga; A. Semang; S. Ghunu (Politeknik Pertanian Negeri Kupang, 2013)
Improving Nutrient Content of Kume Standing Hay (Sorghum plumosum var. Timorense)Fermentedwith StarbioProbiotics. The purpose of this research was to find out the effect of starbio bioconversion on nutritional content of kume standing hay (dry matter, crude protein, crude fiber, neutral detergent fiber, cellulose and hemicellulose). This research had 4 treatments, namely with 0% of starbio (P0), 0.4% (P1). 0.6% (P2),and 0.8% (P3).This study was carried out using Complete Randomized Design with four replications, and if there were significant influence, it would be further tested with Duncan’s Multiple Range Test.The result showed that the addition of 0,8% starbio significantly affected (P<0.01)the content of nutrientsincluding; dry matter (88.60±0.07%), crude protein (6.79±0.03%), crude fiber (28.70±0.53%), neutral detergent fiber (77,40±0,14%), cellulose (30,31±0,38%) and hemicelluloses (20,11±0,12%) compared to basal feed. However no significant effect (P>0.05) found on feed consumption. The conclusion was that the addition of 0.8 % starbio bioconversion significantly gave the best result based on nutrient content of kume standing hay Keywords: Kume standing hay, Bioconvertion, Fermentation, Starbio